Mutual understanding and cooperation between patient and psychotherapist in psychotherapy. Evaluation of the goodness-of-fit of measurement by means of the Working Alliance Inventory (WAI) questionnaire - Prusiński, Tomasz (Przegląd Psychologiczny, 2022)
Objective This article presents the results of the efforts on the Polish adaptation of the WAI questionnaire, gathered from several publications to date and from the current analysis. The tool, after several years of research with its application and estimation of psychometric properties, can be recommended to take measurement of the quality of the psychotherapeutic relationship. Theses The focus is on the key function of the psychotherapeutic relationship towards generating positive performance in the treatment of health problems. Globally there are many tools to assess the quality of a psychotherapeutic relationship. To date the Polish psychologists and psychotherapists have not had such tools at their disposal. Conclusions Analysis of the reliability of three of the four versions of the questionnaire (WAI-PC, WAI-PT, WAI-R, WAI-SUM) showed that the measurement made by the scale can be considered reliable. Evidence is presented verifying the alliance structure in action. Confirmatory factor analysis confirmed the three-dimensional structure of the psychotherapeutic alliance. The WAI questionnaire showed satisfactory theoretical validity. The WAI questionnaire in its 36-item version is a consistent tool that can be successfully used in research.